Metal lithium negative electrode high-entropy current collector and preparation method and application thereof

By constructing a high-entropy coating on the current collector of the lithium-ion battery and depositing a metal lithium film layer, the problem of dendritic growth of lithium metal negative electrodes is solved, and the safety and performance of the battery are improved.

CN119400810AActive Publication Date: 2025-02-07XI AN JIAOTONG UNIV

Patent Information

Application Number
CN202411520998.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2025-02-07
Estimated Expiration
2044-10-29

AI Technical Summary

Technical Problem

Lithium metal negative electrodes have dendritic growth problems in lithium-ion batteries, resulting in short-circuit battery, low Coulomb efficiency and short cycle life.

Method used

Magneto-controlled sputtering technology is used to construct a high-entropy coating on the current collector, and a metal lithium film layer is deposited on its surface, induced metal lithium dendrites and prevented the free growth of lithium dendrites.

Benefits of technology

It effectively avoids short circuit caused by lithium dendrites penetrating into contact with the positive electrode, improves the cycle life and Coulomb efficiency of the lithium battery, and reduces the capacity attenuation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119400810A_ABST
    Figure CN119400810A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of lithium metal battery preparation, and particularly relates to a metal lithium negative electrode high-entropy current collector and a preparation method and application thereof. The preparation method of the metal lithium negative electrode high-entropy current collector comprises the following steps: with a current collector as a substrate, sputtering a high-entropy alloy target material on the current collector substrate by adopting a first magnetron sputtering mode to construct a high-entropy coating; sputtering a metal lithium target material on the surface of the high-entropy current collector by adopting a second magnetron sputtering mode, and depositing to obtain a metal lithium film layer; the metal lithium negative electrode high-entropy current collector is obtained. The high-entropy coating is deposited on the current collector substrate through magnetron sputtering, and due to the physical and chemical properties of the high-entropy coating, the surface energy state is regulated and controlled by regulating and controlling the components of the high-entropy coating, so that the nucleation potential barrier of lithium can be reduced, and the nucleation growth process of the lithium can be regulated and controlled; and lithium is uniformly deposited on the current collector, so that the cycling stability and the cycling coulombic efficiency of the high-specific-energy metal lithium negative electrode are ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium metal battery preparation, and specifically relates to a metal lithium negative electrode high entropy current collector and a preparation method and application thereof. Background Art

[0002] With the rapid development of social economy, new energy electric vehicles, portable electronic devices and other electronic devices are becoming more and more popular. Therefore, the research on energy batteries has become a hot topic in recent years. According to research data in recent years, the current lithium-ion battery with graphite as the negative electrode is very close to its theoretical capacity and it is difficult to improve it significantly. If lithium metal is used to replace graphite as the negative electrode material, the specific capacity of the negative electrode will be increased by more than ten times. However, there are still some problems in the widespread use of high-capacity lithium metal negative electrodes. Among them, the dendritic growth of lithium is one of the key issues, that is, the lithium metal negative electrode will form irregular lithium dendrites during the deposition / deposition of lithium. This dendritic growth pattern will lead to several important problems: (1) When the lithium dendrite grows to a certain extent, it will pierce the diaphragm and cause the battery to short-circuit, posing a serious safety hazard; (2) At the same time, with the continuous deposition of lithium metal, the solid electrolyte interface film on the surface of the negative electrode material will repeatedly break and re-form, continuously consuming active lithium and reducing its coulombic efficiency; (3) In addition, it will also produce irreversible capacity loss. Therefore, controlling the growth process of lithium dendrites is the current research focus.

[0003] At present, there are four promising strategies to deal with the growth of lithium metal dendrites: (1) optimization of the interface between lithium metal anode and solid electrolyte; (2) use of solid electrolyte; (3) structural design of three-dimensional lithium metal anode; (4) optimization and improvement of the separator. However, most of the above-mentioned solutions inhibit the growth of dendrites through physical barriers, and only a few consider the root cause of lithium dendrite growth. They do not fundamentally solve the problem, which can easily lead to lithium dendrites penetrating the separator and contacting the positive electrode, causing short circuits, as well as poor cycle life and coulombic efficiency. Summary of the invention

[0004] The object of the present invention is to provide a metal lithium negative electrode high entropy current collector and its preparation method and application. By constructing a high entropy coating on the current collector through magnetron sputtering technology, the nucleation growth of metal lithium is induced, so that the metal lithium undergoes a dendrite-free deposition process, ensuring that the metal lithium can be uniformly deposited on one side of the negative electrode, and preventing the free growth process of lithium dendrites from the root, avoiding the phenomenon that lithium dendrites penetrate the diaphragm and contact the positive electrode to cause a short circuit, improving the cycle life and coulomb efficiency of high-energy lithium batteries, and also preventing it from causing safety hazards. In addition, a metal lithium film layer of controllable thickness is deposited on the surface of the prepared high entropy current collector using magnetron sputtering technology, overcoming the technical difficulties in preparing ultra-thin lithium foil caused by insufficient ductility of metal lithium. In addition, the use of magnetron sputtering technology to deposit metal lithium foil also helps the interface contact between metal lithium and the current collector, reducing contact resistance.

[0005] To achieve the above objectives, the present invention solves the above technical problems through the following technical solutions.

[0006] The first object of the present invention is to provide a method for preparing a metal lithium negative electrode high entropy current collector, comprising the following steps:

[0007] With the current collector as the substrate, a high entropy alloy target is sputtered on the current collector substrate by a first magnetron sputtering method to construct a high entropy coating.

[0008] The metal lithium target is sputtered onto the surface of the high entropy current collector by a second magnetron sputtering method to deposit a metal lithium film layer, that is, a metal lithium negative electrode high entropy current collector is obtained.

[0009] Furthermore, the high entropy elements in the high entropy coating are three or more of scandium, titanium, vanadium, chromium, manganese, iron, cobalt, nickel, copper, zinc, yttrium, zirconium, niobium, molybdenum, technetium, ruthenium, rhodium, hafnium, tantalum, tungsten, rhenium, lanthanum, cerium, praseodymium, neodymium, promethium, and samarium. In the high entropy alloy coating, the atomic percentage of each high entropy element is equal, and the sum of the atomic percentages of each high entropy element is 100%.

[0010] Furthermore, the high entropy coating is a high entropy alloy coating, a high entropy alloy oxide coating or a high entropy alloy nitride coating.

[0011] Furthermore, in the process of sputtering the high entropy alloy target on the current collector substrate, the gas for magnetron sputtering is argon, oxygen or nitrogen, and the gas pressure is 0.25Pa~0.35Pa. When the gas for magnetron sputtering is argon, the high entropy coating is a high entropy alloy coating, when the gas for magnetron sputtering is oxygen, the high entropy coating is a high entropy alloy oxide coating, and when the gas for magnetron sputtering is nitrogen, the high entropy coating is a high entropy alloy nitride coating; in the process of sputtering the metal lithium target on the surface of the high entropy current collector, the gas for magnetron sputtering is argon, and the gas pressure is 0.25Pa~0.35Pa.

[0012] Furthermore, the current collector substrate is copper foil, polymer-based composite copper foil or aluminum-copper composite substrate.

[0013] Further, the method specifically includes the following steps:

[0014] The raw materials of high entropy elements are mixed according to atomic proportions and then ball-milled, and then flash-fired to form a high entropy alloy target material, the purity of which is ≥99.99%.

[0015] A winding DC magnetron reaction device was used to install the current collector substrate on the sample roller. The high entropy alloy target was cleaned with acetone and then dried. It was assembled at the magnetron sputtering cathode and pre-sputtered for 5 minutes to remove oxides and other impurities on the target surface. Then DC magnetron reactive sputtering was performed to sputter the high entropy alloy target onto the current collector substrate.

[0016] Then, a metal lithium target is sputtered onto the surface of a high entropy current collector using a winding DC magnetron reactive sputtering method, the current collector substrate sputtered with a high entropy coating is mounted on a sample roller, the metal lithium target is cleaned with acetone and then dried, assembled at the magnetron sputtering cathode, pre-sputtered for 5 minutes to remove oxides and other impurities on the target surface, and then DC magnetron reactive sputtering is performed to sputter the metal lithium target onto the surface of the high entropy current collector to obtain a metal lithium negative electrode high entropy current collector.

[0017] Furthermore, the raw material of the high entropy element comes from elemental metal powder and / or alloy metal powder, and the purity of the elemental metal powder and the alloy metal powder is not less than 99.99%.

[0018] Furthermore, during the DC magnetron reactive sputtering process, the vacuum degree of magnetron sputtering was 9.9×10 -5 Pa~50×10 -5 Pa, target distance is 20cm~50cm, sputtering temperature is 20℃~30℃, and winding / unwinding speed of the winding roller is 5rpm~10rpm.

[0019] The second object of the present invention is to provide a metallic lithium negative electrode high entropy current collector prepared by the above preparation method, in which the thickness of the high entropy coating is 20nm to 200nm, and the thickness of the metallic lithium film layer is 5μm to 30μm.

[0020] The third object of the present invention is to provide an application of the above-mentioned metal lithium negative electrode high entropy current collector in a lithium battery, wherein the lithium battery comprises a positive electrode, a separator, a metal lithium negative electrode high entropy current collector and an electrolyte, wherein the positive electrode is one of lithium cobalt oxide, lithium nickel manganese cobalt oxide, lithium nickel aluminum cobalt oxide, and a lithium-rich manganese-based material, and the separator is a polyethylene separator or a polypropylene microporous separator; and the electrolyte is a mixture of lithium hexafluorophosphate, dimethyl carbonate and diethyl carbonate.

[0021] Furthermore, the preparation process of the positive electrode includes the following steps: dispersing the positive electrode material, Super-P and polyvinylidene fluoride in N-methylpyrrolidone at a mass ratio of 90:5:5 by vacuum stirring to form a positive electrode slurry with a viscosity of 1Pa·s to 10Pa·s, scraping the above positive electrode slurry onto the surface of the aluminum foil, vacuum drying at 100°C for 2h and then rolling to prepare a positive electrode sheet. The prepared positive electrode surface loading is 1mAh / cm 2 ~5mAh / cm 2 .

[0022] Furthermore, the concentration of lithium hexafluorophosphate in the electrolyte is 1 mol / L to 5 mol / L, and the volume ratio of dimethyl carbonate to diethyl carbonate is 1:1.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] (1) The present invention provides a method for preparing an ultra-thin metal lithium negative electrode high entropy current collector for a lithium battery. The high entropy coating is constructed on the current collector substrate by a magnetron sputtering method, and a metal lithium film layer is deposited on the surface of the high entropy coating to form a metal lithium negative electrode high entropy current collector. The high entropy coating induces the nucleation and growth of metal lithium, so that the metal lithium undergoes a dendrite-free deposition process to form a metal lithium film layer, ensuring that the metal lithium can be uniformly deposited on one side of the negative electrode, fundamentally preventing the free growth process of lithium dendrites, and avoiding the phenomenon that lithium dendrites penetrate the diaphragm and contact the positive electrode to cause a short circuit. The present invention is based on thermodynamics and kinetics, and by preparing a nanoscale high entropy coating on the surface of the negative electrode current collector, lithium can be uniformly deposited on one side of the current collector attached with the nanoscale high entropy coating, thereby achieving spatial control of the lithium deposition process. The addition of a functional high entropy coating reduces the free growth of lithium dendrites, eliminates the possibility of lithium dendrites penetrating the diaphragm and contacting the positive electrode to cause a short circuit, improves its coulomb efficiency and cycle life, and reduces its capacity attenuation.

[0025] (2) The high entropy coating provided by the present invention has an intricate lattice structure, which will produce obvious lattice deformation, thereby generating a large number of dislocations and defects. At the same time, the uniform distribution of the constituent elements induces an increase in configurational entropy, thereby producing a high entropy effect. In addition, the performance of the alloy benefits from the synergistic effect of different constituent elements, exceeding that of single-element materials and traditional alloy materials. These characteristics of high entropy materials lead to some unique properties, such as the generation of multiple lithium ion transmission paths, active sites and high ionic conductivity. Compared with traditional alloys, the synergistic effect of multiple elements in high entropy materials can adjust the lithium affinity characteristics to increase the adsorption and diffusion energy, thereby promoting the uniformity of lithium deposition.

[0026] (2) The present invention discloses a method for preparing a high-entropy current collector for an ultra-thin metal lithium negative electrode of a lithium battery. The preparation method deposits a nano-scale high-entropy alloy coating, a high-entropy oxide coating or a high-entropy nitride coating on the surface of an existing current collector substrate by a DC magnetron sputtering process, and then deposits an ultra-thin metal lithium layer. Due to the physical and chemical properties of the high-entropy coating itself, the surface energy state is regulated by regulating the composition of the high-entropy coating. In addition, the nucleation barrier of lithium can be reduced, and its nucleation growth process can be regulated, so that lithium is uniformly deposited on the current collector to ensure the cycle stability and cycle coulomb efficiency of the high-energy metal lithium negative electrode. It has been verified that the charge and discharge cycle performance of the lithium battery using the current collector is significantly improved, which is specifically manifested in that as the number of cycles increases, and after 200 cycles, the coulomb efficiency remains at a high level; therefore, the battery using the current collector improves the safety performance of the battery, and also improves its cycle life and coulomb efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 It is the coulombic efficiency of the metal lithium negative electrode cycle of Example 1 of the present invention. DETAILED DESCRIPTION

[0028] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0029] It should be noted that the professional terms used in the present invention are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention. Unless otherwise specifically stated, the various raw materials, reagents, instruments and equipment used in the following embodiments of the present invention can be purchased from the market or prepared by existing methods.

[0030] At present, there are mainly the following ways to deal with the problem of lithium metal dendrite growth: (1) optimization of the interface between lithium metal negative electrode and solid electrolyte; (2) use of solid electrolyte; (3) structural design of three-dimensional lithium metal negative electrode; (4) optimization and improvement of the diaphragm. However, most of the above-mentioned solutions inhibit the growth of dendrites by physical hindrance, and only a few consider the root cause of lithium dendrite growth, that is, its nucleation process. The nucleation process of lithium dendrites occurs during the electrochemical deposition process. In addition, due to the presence of non-uniform electric field and lithium ion flux in the liquid electrolyte system, its nucleation is usually non-uniform, which promotes the growth process of lithium dendrites to a certain extent. To this end, the present invention provides an excellent high-energy-density lithium battery ultra-thin metal lithium negative electrode and high-entropy current collector integrated structure and its preparation method, and a lithium battery using the ultra-thin metal lithium negative electrode high-entropy current collector.

[0031] Based on the above problems, the present invention provides a method for preparing a metal lithium negative electrode high entropy current collector, comprising the following steps:

[0032] Taking the current collector as the substrate, a high entropy alloy target is sputtered on the current collector substrate by a first magnetron sputtering method to construct a high entropy coating;

[0033] The metal lithium target is sputtered onto the surface of the high entropy current collector by a second magnetron sputtering method to deposit a metal lithium film layer, that is, a metal lithium negative electrode high entropy current collector is obtained.

[0034] The present invention provides a method for preparing an ultra-thin metal lithium negative electrode high entropy current collector for a lithium battery. A high entropy coating is constructed on a current collector substrate by a magnetron sputtering method, and a metal lithium film layer is deposited on the surface of the high entropy coating to form a metal lithium negative electrode high entropy current collector. The high entropy coating induces the nucleation and growth of metal lithium, so that the metal lithium undergoes a dendrite-free deposition process to form a metal lithium film layer, thereby ensuring that the metal lithium can be uniformly deposited on one side of the negative electrode, thereby preventing the free growth process of lithium dendrites from the root, and avoiding the phenomenon that lithium dendrites penetrate the diaphragm and contact the positive electrode to cause a short circuit. The present invention is based on thermodynamics and kinetics, and by preparing a nanoscale high entropy coating on the surface of the negative electrode current collector, lithium can be uniformly deposited on one side of the current collector to which the nanoscale high entropy coating is attached, thereby realizing spatial control of the lithium deposition process. The addition of a functional high entropy coating reduces the free growth of lithium dendrites, eliminates the possibility that lithium dendrites penetrate the diaphragm and contact the positive electrode to cause a short circuit, improves its coulomb efficiency and cycle life, and reduces its capacity attenuation.

[0035] Compared with the prior art, the present invention is based on thermodynamics and kinetics, and by preparing a nano-scale high entropy coating on the surface of the negative electrode current collector, lithium can be uniformly deposited on one side of the current collector with the nano-scale high entropy coating attached, thereby spatially controlling the deposition process of lithium. The addition of the functional high entropy coating reduces the free growth of lithium dendrites, eliminates the possibility of lithium dendrites penetrating the diaphragm and contacting the positive electrode to cause a short circuit, improves its coulombic efficiency and cycle life, and reduces its capacity attenuation.

[0036] In a specific embodiment, the high entropy elements in the high entropy coating are three or more of scandium, titanium, vanadium, chromium, manganese, iron, cobalt, nickel, copper, zinc, yttrium, zirconium, niobium, molybdenum, technetium, ruthenium, rhodium, hafnium, tantalum, tungsten, rhenium, lanthanum, cerium, praseodymium, neodymium, promethium, and samarium. In the high entropy coating, the atomic percentage of each high entropy element is equal, and the sum of the atomic percentages of each high entropy element is 100%.

[0037] The present invention provides a high-entropy current collector for an ultra-thin metal lithium negative electrode of a lithium battery, wherein the high-entropy coating has an intricate lattice structure, which produces obvious lattice deformation, thereby generating a large number of dislocations and defects; at the same time, the uniform distribution of the constituent elements induces an increase in configurational entropy, thereby generating a high-entropy effect. In addition, the performance of the alloy benefits from the synergistic effect of different constituent elements, exceeding that of single-element materials and traditional alloy materials. These characteristics of high-entropy materials lead to some unique properties, such as the generation of multiple lithium ion transmission paths, active sites, and high ionic conductivity. Compared with traditional alloys, the synergistic effect of multiple elements of high-entropy materials can adjust the lithium-philic properties to increase the adsorption and diffusion energy, thereby promoting the uniformity of lithium deposition. Therefore, the research and development of a negative electrode current collector with high entropy is crucial to achieve uniform lithium deposition with ultra-stable performance.

[0038] In a specific embodiment, the high entropy coating is a high entropy alloy coating, a high entropy alloy oxide coating or a high entropy alloy nitride coating. The entropy coating of the present invention is a nanoscale high entropy coating, and each component element of the high entropy coating is sputtered and deposited on the current collector substrate by magnetron sputtering to form a high entropy coating. The physical and chemical properties of the high entropy coating itself are regulated by regulating the composition of the high entropy coating to regulate the surface energy state, thereby reducing the nucleation barrier of lithium, regulating its nucleation growth process, and making lithium uniformly deposited on the current collector to ensure the cycle stability and cycle coulomb efficiency of the high specific energy metal lithium negative electrode.

[0039] In a specific embodiment, during the sputtering of the high entropy alloy target on the current collector substrate, the vacuum degree of magnetron sputtering is 9.9×10 -5 Pa~50×10 -5Pa, the gas for magnetron sputtering is argon, oxygen or nitrogen, the gas pressure is 0.25Pa~0.35Pa, the target distance is 20cm~50cm, the sputtering temperature is 20℃~30℃, and the unwinding / winding speed of the winder is 5rpm~10rpm.

[0040] In a specific embodiment, during the sputtering of the lithium metal target onto the surface of the high entropy current collector, the vacuum degree of the magnetron sputtering is 9.9×10 -5 Pa~50×10 -5 Pa, the gas for magnetron sputtering is argon, the gas pressure is 0.25Pa~0.35Pa, the target distance is 20cm~50cm, the sputtering temperature is 20℃~30℃, and the unwinding / winding speed of the winder is 5rpm~10rpm.

[0041] In a specific embodiment, when the high entropy alloy target is sputtered on the current collector substrate, when the magnetron sputtering gas is argon, the high entropy coating is a high entropy alloy coating; when the magnetron sputtering gas is oxygen, the high entropy coating is a high entropy alloy oxide coating; when the magnetron sputtering gas is nitrogen, the high entropy coating is a high entropy alloy nitride coating.

[0042] In a specific embodiment, the current collector substrate is a cold-rolled copper foil, a polymer-based composite copper foil or an aluminum-copper composite current collector. In the present invention, the cold-rolled copper foil is a pure copper foil, and the polymer in the polymer-based composite copper foil can be polyacrylonitrile or polymethyl methacrylate.

[0043] In a specific embodiment, the preparation method of the metal lithium negative electrode high entropy current collector specifically comprises the following steps:

[0044] The raw materials of high entropy elements are mixed according to atomic proportions and then ball-milled, and then flash-fired to form a high entropy alloy target material, the purity of which is ≥99.99%.

[0045] A winding DC magnetron reaction device was used to install the current collector substrate on the sample roller. The high entropy alloy target was cleaned with acetone and then dried. It was assembled at the magnetron sputtering cathode and pre-sputtered for 5 minutes to remove oxides and other impurities on the target surface. Then DC magnetron reactive sputtering was performed to sputter the high entropy alloy target onto the current collector substrate.

[0046] Then, a metal lithium target is sputtered onto the surface of a high entropy current collector using a winding DC magnetron reactive sputtering method, the current collector substrate sputtered with a high entropy coating is mounted on a sample roller, the metal lithium target is cleaned with acetone and then dried, assembled at the magnetron sputtering cathode, pre-sputtered for 5 minutes to remove oxides and other impurities on the target surface, and then DC magnetron reactive sputtering is performed to sputter the metal lithium target onto the surface of the high entropy current collector to obtain a metal lithium negative electrode high entropy current collector.

[0047] In the present invention, the flash method is an electric field assisted ceramic sintering method, in which a stable electric field is applied to the material, and the furnace temperature is increased at a constant rate. When the furnace temperature is low, the resistivity of the material is high, and the current flowing through the material is very small. As the furnace temperature increases, the resistivity of the sample decreases, and the current gradually increases. This stage is called the incubation stage, and the system is voltage controlled. When the furnace temperature rises to the critical temperature, the resistivity of the material drops suddenly, the current rises sharply, and flash occurs. Since the field strength is still stable at this time, the system power (W=EJ) will quickly reach the upper limit of the power supply, and the system changes from voltage control to current control. This stage is called the flash stage. In the present invention, the flash method is an existing conventional technology, and as long as it can be formed into a high entropy alloy target, the present invention will not be further explained.

[0048] The present invention deposits a nano-scale high entropy alloy coating, a high entropy oxide coating or a high entropy nitride coating on the surface of an existing current collector substrate by a DC magnetron sputtering process, and then deposits an ultra-thin metal lithium layer. It has been verified that the charge and discharge cycle performance of the lithium battery using the current collector is significantly improved, which is specifically manifested in that as the number of cycles increases, and after 200 cycles, the coulomb efficiency remains at a high level; therefore, the battery using the current collector improves the safety performance of the battery, and also improves its cycle life and coulomb efficiency.

[0049] In a specific embodiment, the raw material of the high entropy element comes from elemental metal powder and / or alloy metal powder, and the purity of the elemental metal powder and the alloy metal powder is not less than 99.99%.

[0050] The present invention also provides a metal lithium negative electrode high entropy current collector prepared by the above preparation method, in which the thickness of the high entropy coating is 20nm to 200nm, and the thickness of the metal lithium film layer is 5μm to 30μm. In the present invention, the thickness of the high entropy coating can be any value between 20nm and 200nm, such as 20nm, 50nm, 100nm, 150nm or 200nm, and the thickness of the metal lithium film layer can be any value between 5μm and 30μm, such as 5μm, 10μm, 15μm, 20μm, 25μm or 30μm, but it is not limited to the specific values ​​listed, and other values ​​not listed within the above value range are also applicable, so they will not be repeated here.

[0051] In addition, the present invention also provides an application of a metal lithium negative electrode high entropy current collector in a lithium battery. The lithium battery consists of a positive electrode, a diaphragm, a metal lithium negative electrode high entropy current collector and an electrolyte. The positive electrode is one of lithium cobalt oxide, lithium nickel manganese cobalt oxide, lithium nickel aluminum cobalt oxide, and a lithium-rich manganese-based material. The diaphragm is a polyethylene diaphragm or a polypropylene microporous diaphragm; and the electrolyte is a mixture of lithium hexafluorophosphate, dimethyl carbonate and diethyl carbonate.

[0052] In a specific embodiment, the preparation process of the positive electrode includes the following steps: dispersing the positive electrode material, Super-P conductive agent and polyvinylidene fluoride in N-methylpyrrolidone at a mass ratio of 90:5:5 by vacuum stirring to form a positive electrode slurry with a viscosity of 1Pa·s to 10Pa·s, scraping the above positive electrode slurry onto the surface of the aluminum foil, vacuum drying at 100°C for 2h and then rolling to prepare a positive electrode sheet, and the prepared positive electrode surface loading is 1mAh / cm 2 ~5mAh / cm 2 .

[0053] In a specific embodiment, the concentration of lithium hexafluorophosphate in the electrolyte is 1-5 mol / L, and the volume ratio of dimethyl carbonate to diethyl carbonate is 1:1.

[0054] The invention is further described below through specific examples.

[0055] Example 1

[0056] Preparation of ultra-thin lithium metal negative electrode niobium molybdenum tantalum hafnium high entropy current collector (Li-NbMoTaHf-Cu) and its application in NCM811 full battery, including the following steps:

[0057] S1, NbMoTaHf high entropy alloy target sintering

[0058] Nb, Mo, Ta, Hf metal powders with a purity of 99.99% are dispersed in acetone at a mass ratio of 1:1:1:1 and mixed using a planetary ball mill. The dried mixed metal powder is then pressed into the required sputtering target size and then flash-sintered to form a NbMoTaHf high entropy alloy target for sputtering, with a purity of ≥99.99%.

[0059] Preparation of S2 and NbMoTaHf-Cu high entropy current collector

[0060] The pre-purchased copper foil substrate (commercial copper foil) was mounted on the sample roller. According to the pre-prepared niobium, molybdenum, tantalum and hafnium high entropy alloy target, the target was cleaned with acetone and dried, and then assembled at the magnetron sputtering cathode. Pre-sputtering for 5 minutes was performed to remove oxides and other impurities on the target surface. The sample roller and the roller were turned on, the speed was set to 5rpm, and the cathode power supply of the niobium, molybdenum, tantalum and hafnium high entropy alloy target was turned on to start sputtering the niobium, molybdenum, tantalum and hafnium high entropy alloy to form a NbMoTaHf high entropy alloy coating, and a NbMoTaHf-Cu current collector was prepared; the thickness of the copper foil substrate was 12μm, the thickness of the NbMoTaHf high entropy alloy coating was 50nm, and the process parameters of the magnetron sputtering were: the vacuum degree was 5.0×10 -4 Pa, sputtering power 120W, working gas pressure 0.35Pa, working gas is argon, target distance is 40cm, and sputtering temperature is 25℃.

[0061] S3. Preparation of ultra-thin lithium metal negative electrode high entropy current collector integrated structure Li-NbMoTaHf-Cu

[0062] The ultra-thin metal lithium anode was deposited on the surface of the NbMoTaHf-Cu current collector using magnetron sputtering technology, and the sample roller speed was set to 5 rpm. The process parameters of magnetron sputtering were: the background vacuum was 5.0×10 -4 Pa, sputtering power 70W, working pressure 0.35Pa, working gas is argon, target distance is 40cm, sputtering temperature is 25℃. The thickness of deposited metal lithium is 30μm. The Li-NbMoTaHf-Cu current collector carrying ultra-thin metal lithium anode is punched into the required shape for subsequent NCM811 full battery assembly.

[0063] S4, NCM811-Al cathode preparation

[0064] NCM811 cathode material powder, Super-P conductive agent and polyvinylidene fluoride were dispersed in N-methylpyrrolidone at a mass ratio of 90:5:5 by vacuum stirring to form NCM811 slurry with a viscosity of 5 Pa·s. The above cathode slurry was scraped onto the surface of aluminum foil, vacuum dried at 100°C for 2h, and then rolled and punched into the desired shape to prepare Al-NCM811 cathode sheet. The prepared cathode surface loading was 5 mAh / cm 2 .

[0065] S5. Preparation of electrolyte

[0066] Dimethyl carbonate and diethyl carbonate were mixed in equal volumes, and lithium hexafluorophosphate was dispersed in the mixed solution to prepare an electrolyte solution with a lithium hexafluorophosphate concentration of 1 mol / L.

[0067] S6, High specific energy lithium battery Al-NCM811|Li-NbMoTaHf-Cu battery cell assembly

[0068] Ten pieces of ultra-thin metal lithium negative electrode high entropy current collector integrated structure Li-NbMoTaHf-Cu prepared by S3, 11 pieces of positive electrode NCM811-Al prepared by S4 and polyethylene separator were stacked to prepare high specific energy lithium battery cells, and then the cells were placed in pre-punched aluminum-plastic bags. After drying at 100°C for 20 hours, the electrolyte prepared by S5 was injected, and the amount of electrolyte added was 3g / Ah. The prepared Al-NCM811|Li-NbMoTaHf-Cu battery cells were then subjected to formation treatment, and the formation process was: charging at a constant current and constant voltage rate of 0.1C to 4.3V, and discharging at a constant current rate of 0.1C to 3.0V. After the formation treatment, the exhaust was finally sealed and the label was attached for storage.

[0069] The charge and discharge comparison test of the original copper foil and the ultra-thin metal lithium negative electrode high entropy current collector integrated structure prepared in Example 1 found that when the NbMoTaHf high entropy alloy coating of the present invention is sputtered on the current collector, the nucleation barrier of lithium is reduced, and the deposition of lithium can be controlled spatially, so that lithium is uniformly deposited on the current collector attached with the NbMoTaHf high entropy alloy coating, which prevents the free growth of lithium dendrites, thereby avoiding the safety hazards such as internal short circuit of the battery caused by contact between dendrites and the positive electrode. The charge and discharge cycle performance of the metal lithium negative electrode is significantly improved, which is specifically manifested in that the capacity of the battery remains stable as the number of cycles increases, and after 200 cycles, the coulomb efficiency remains at a high level.

[0070] Example 2

[0071] Preparation of ultra-thin lithium metal negative electrode tantalum niobium hafnium zirconium high entropy current collector (Li-TaNbHfZr-Cu) and its application in NCM811 full battery, including the following steps:

[0072] S1. TaNbHfZr high entropy alloy target sintering

[0073] Nb, Zr, Ta, Hf metal powders with a purity of 99.99% are dispersed in acetone at a mass ratio of 1:1:1:1 and mixed using a planetary ball mill. The dried mixed metal powder is then pressed into the required sputtering target size and then flash-sintered to form a TaNbHfZr high entropy alloy target for sputtering, with a purity of ≥99.99%.

[0074] Preparation of S2, TaNbHfZr-Cu high entropy current collector

[0075] The pre-purchased copper foil was mounted on the sample roller. According to the pre-made niobium, molybdenum, tantalum and hafnium high entropy alloy target, the target was cleaned with acetone and dried, and then assembled on the magnetron sputtering cathode. Pre-sputtering for 5 minutes was performed to remove oxides and other impurities on the surface of the target. The sample roller and the roller were turned on, the speed was set to 5rpm, and the cathode power supply of the niobium, molybdenum, tantalum and hafnium high entropy alloy target was turned on to start sputtering the niobium, molybdenum, tantalum and hafnium high entropy alloy to form a TaNbHfZr-Cu high entropy alloy coating and prepare a TaNbHfZr-Cu current collector; the thickness of the copper foil substrate was 12μm, the thickness of the TaNbHfZr-Cu high entropy alloy coating was 50nm, and the process parameters of the magnetron sputtering were: the background vacuum was 5.0×10 -4 Pa, sputtering power 110W, working gas pressure 0.35Pa, working gas is argon, target distance is 40cm, and sputtering temperature is 25℃.

[0076] S3. Preparation of ultra-thin lithium metal negative electrode high entropy current collector integrated structure Li-TaNbHfZr-Cu

[0077] The ultra-thin metal lithium anode was deposited on the surface of the TaNbHfZr-Cu current collector using magnetron sputtering technology, and the sample roller speed was set to 5 rpm. The process parameters of magnetron sputtering were: the background vacuum was 5.0×10 -4 Pa, sputtering power 70W, working pressure 0.35Pa, working gas is argon, target distance is 40cm, sputtering temperature is 25℃. The thickness of deposited metal lithium is 30μm. The Li-TaNbHfZr-Cu current collector carrying ultra-thin metal lithium anode is punched into the required shape for subsequent NCM811 full battery assembly.

[0078] S4, NCM811-Al cathode preparation

[0079] NCM811 cathode material powder, Super-P and polyvinylidene fluoride were dispersed in N-methylpyrrolidone at a mass ratio of 90:5:5 by vacuum stirring to form NCM811 slurry with a viscosity of 5 Pa·s. The above cathode slurry was scraped onto the surface of aluminum foil, vacuum dried at 100°C for 2 hours, and then rolled and punched into the desired shape to prepare Al-NCM811 cathode sheet. The prepared cathode surface loading was 5 mAh / cm 2 .

[0080] S5. Preparation of electrolyte

[0081] Dimethyl carbonate and diethyl carbonate were mixed in equal volumes, and lithium hexafluorophosphate was dispersed in the mixed solution to prepare an electrolyte solution with a lithium hexafluorophosphate concentration of 1 mol / L.

[0082] S6, High energy density lithium battery Al-NCM811|Li-TaNbHfZr-Cu cell assembly

[0083] Ten pieces of ultra-thin metal lithium negative electrode high entropy current collector integrated structure Li-TaNbHfZr-Cu prepared by S3, 11 pieces of positive electrode NCM811-Al prepared by S4 and polyethylene separator were stacked to prepare high specific energy lithium battery cells, and then the cells were placed in a pre-punched aluminum-plastic bag. After drying at 100°C for 20 hours, the electrolyte prepared by S5 was injected, and the amount of electrolyte added was 3g / Ah. The prepared Al-NCM811|Li-TaNbHfZr-Cu battery cell was then subjected to formation treatment, and the formation process was: charging at a constant current and constant voltage rate of 0.1C to 4.3V, and discharging at a constant current rate of 0.1C to 3.0V. After the formation treatment, the exhaust was finally sealed and the label was attached for storage.

[0084] The charge and discharge comparison test of the original copper foil and the ultra-thin metal lithium negative electrode high entropy current collector integrated structure prepared in Example 2 found that when the TaNbHfZr high entropy alloy coating of the present invention is sputtered on the current collector, the nucleation barrier of lithium is reduced, and the deposition of lithium can be controlled spatially, so that lithium is uniformly deposited on the current collector attached with the TaNbHfZr high entropy alloy coating, which prevents the free growth of lithium dendrites, thereby avoiding the safety hazards such as internal short circuit of the battery caused by contact between dendrites and the positive electrode. The charge and discharge cycle performance of the metal lithium negative electrode is significantly improved, which is specifically manifested in that the capacity of the battery remains stable as the number of cycles increases, and after 200 cycles, the coulomb efficiency remains at a high level.

[0085] Example 3

[0086] Preparation of ultra-thin lithium metal anode zirconium tantalum niobium titanium tungsten high entropy current collector (Li-ZrTaNbTiW-Cu) and its application in NCM811 full battery

[0087] S1. ZrTaNbTiW high entropy alloy target sintering

[0088] Nb, Zr, Ta, Ti, and W metal powders with a purity of 99.99% are dispersed in acetone at a mass ratio of 1:1:1:1:1 and mixed using a planetary ball mill. The dried mixed metal powder is then pressed into the required sputtering target size and then flash-sintered to form a ZrTaNbTiW high entropy alloy target for sputtering, with a purity of ≥99.99%.

[0089] S2, ZrTaNbTiW-Cu high entropy current collector preparation

[0090] The pre-purchased copper foil was installed on the sample roller. According to the pre-prepared niobium, molybdenum, tantalum and hafnium high entropy alloy target, the target was cleaned with acetone and dried, and then assembled on the magnetron sputtering cathode. Pre-sputtering for 5 minutes was performed to remove oxides and other impurities on the surface of the target. The sample roller and the roller were turned on, the speed was set to 5rpm, and the cathode power supply of the niobium, molybdenum, tantalum and hafnium high entropy alloy target was turned on to start sputtering the niobium, molybdenum, tantalum and hafnium high entropy alloy to form a ZrTaNbTiW-Cu high entropy alloy coating, and a ZrTaNbTiW-Cu current collector was prepared. The thickness of the copper foil substrate was 12μm, the thickness of the ZrTaNbTiW-Cu high entropy alloy coating was 50nm, and the process parameters of the magnetron sputtering were: the background vacuum was 5.0×10 -4 Pa, sputtering power 110W, working gas pressure 0.35Pa, working gas is argon, target distance is 40cm, and sputtering temperature is 25℃.

[0091] S3. Preparation of ultra-thin lithium metal negative electrode high entropy current collector integrated structure Li-ZrTaNbTiW-Cu

[0092] The ultra-thin metal lithium anode was deposited on the surface of the ZrTaNbTiW-Cu current collector by magnetron sputtering technology, and the sample roller speed was set to 5 rpm. The process parameters of magnetron sputtering were: the background vacuum degree was 5.0×10 -4 Pa, sputtering power 70W, working pressure 0.35Pa, working gas is argon, target distance is 40cm, sputtering temperature is 25℃. The thickness of deposited metal lithium is 30μm. The Li-ZrTaNbTiW-Cu current collector carrying ultra-thin metal lithium anode is punched into the required shape for subsequent NCM811 full battery assembly.

[0093] S4, NCM811-Al cathode preparation

[0094] NCM811 cathode material powder, Super-P and polyvinylidene fluoride were dispersed in N-methylpyrrolidone at a mass ratio of 90:5:5 by vacuum stirring to form NCM811 slurry with a viscosity of 5 Pa·s. The above cathode slurry was scraped onto the surface of aluminum foil, vacuum dried at 100°C for 2h, and then rolled and punched into the desired shape to prepare Al-NCM811 cathode sheet. The prepared cathode surface loading was 5 mAh / cm 2 .

[0095] S5. Preparation of electrolyte

[0096] Dimethyl carbonate and diethyl carbonate were mixed in equal volumes, and lithium hexafluorophosphate was dispersed in the mixed solution to prepare an electrolyte solution with a lithium hexafluorophosphate concentration of 1 mol / L.

[0097] S6, High energy density lithium battery Al-NCM811|Li-ZrTaNbTiW-Cu battery cell assembly

[0098] Ten pieces of ultra-thin metal lithium negative electrode high entropy current collector integrated structure Li-ZrTaNbTiW-Cu prepared by S3, 11 pieces of positive electrode NCM811-Al prepared by S4 and polyethylene separator were stacked to prepare high specific energy lithium battery cells, and then the cells were placed in pre-punched aluminum-plastic bags. After drying at 100°C for 20 hours, the electrolyte prepared by S5 was injected, and the amount of electrolyte added was 3g / Ah. The prepared Al-NCM811|Li-ZrTaNbTiW-Cu battery cells were then subjected to chemical treatment, and the chemical process was: charging at a constant current and constant voltage rate of 0.1C to 4.3V, and discharging at a constant current rate of 0.1C to 3.0V. After the chemical treatment, the exhaust was finally sealed and the label was attached for storage.

[0099] The charge and discharge comparison test of the original copper foil and the ultra-thin metal lithium negative electrode high entropy current collector integrated structure prepared in Example 3 found that when the ZrTaNbTiW high entropy alloy coating of the present invention is sputtered on the current collector, the nucleation barrier of lithium is reduced, and the deposition of lithium can be controlled spatially, so that lithium is uniformly deposited on the current collector attached with the ZrTaNbTiW high entropy alloy coating, which prevents the free growth of lithium dendrites, thereby avoiding the safety hazards such as internal short circuit of the battery caused by contact between dendrites and the positive electrode. The charge and discharge cycle performance of the metal lithium negative electrode is significantly improved, which is specifically manifested in that the capacity of the battery remains stable as the number of cycles increases, and after 200 cycles, the coulomb efficiency remains at a high level.

[0100] Example 4

[0101] Preparation of ultra-thin lithium metal anode hafnium niobium titanium vanadium zirconium nitride high entropy current collector (Li-(HfNbTiVZr)N-Cu) and its application in NCM811 full battery

[0102] S1, HfNbTiVZr high entropy alloy target sintering

[0103] Nb, Hf, Ti, Ti, V metal powders with a purity of 99.99% are dispersed in acetone at a mass ratio of 1:1:1:1:1 and mixed using a planetary ball mill. The dried mixed metal powder is then pressed into the required sputtering target size and then flash-sintered to form a HfNbTiVZr high entropy alloy target for sputtering, with a purity of ≥99.99%.

[0104] S2. Preparation of (HfNbTiVZr)N-Cu high entropy current collector

[0105] The pre-purchased copper foil was installed on the sample roller. According to the pre-prepared niobium, molybdenum, tantalum and hafnium high entropy alloy target, the target was cleaned with acetone and dried, and then assembled on the magnetron sputtering cathode. Pre-sputtering for 5 minutes was performed to remove oxides and other impurities on the surface of the target. The sample roller and the roller were turned on, the speed was set to 5rpm, and the cathode power supply of the niobium, molybdenum, tantalum and hafnium high entropy alloy target was turned on to start sputtering the niobium, molybdenum, tantalum and hafnium high entropy alloy to form a (HfNbTiVZr)N-Cu high entropy alloy coating, and the (HfNbTiVZr)N-Cu current collector was prepared. The thickness of the copper foil substrate was 12μm, the thickness of the (HfNbTiVZr)N-Cu high entropy alloy coating was 50nm, and the process parameters of the magnetron sputtering were: the background vacuum was 5.0×10 -4 Pa, sputtering power 100W, working gas pressure 0.35Pa, working gas is nitrogen, target distance is 40cm, and sputtering temperature is 25℃.

[0106] S3. Preparation of ultra-thin lithium metal negative electrode high entropy current collector integrated structure Li-(HfNbTiVZr)N-Cu

[0107] The ultra-thin metal lithium anode was deposited on the surface of the (HfNbTiVZr)N-Cu current collector by magnetron sputtering technology, and the sample roller speed was set to 5rpm. The process parameters of magnetron sputtering were: the background vacuum was 5.0×10 -4 Pa, sputtering power 70W, working pressure 0.35Pa, working gas is argon, target distance is 40cm, sputtering temperature is 25℃. The thickness of deposited metal lithium is 30μm. The Li-(HfNbTiVZr)N-Cu current collector carrying ultra-thin metal lithium anode is punched into the required shape for subsequent NCM811 full battery assembly.

[0108] S4, NCM811-Al cathode preparation

[0109] NCM811 cathode material powder, Super-P and polyvinylidene fluoride were dispersed in N-methylpyrrolidone at a mass ratio of 90:5:5 by vacuum stirring to form NCM811 slurry with a viscosity of 5 Pa·s. The above cathode slurry was scraped onto the surface of aluminum foil, vacuum dried at 100°C for 2h, and then rolled and punched into the desired shape to prepare Al-NCM811 cathode sheet. The prepared cathode surface loading was 5 mAh / cm 2 .

[0110] S5. Preparation of electrolyte

[0111] Dimethyl carbonate and diethyl carbonate were mixed in equal volumes, and lithium hexafluorophosphate was dispersed in the mixed solution to prepare an electrolyte solution with a lithium hexafluorophosphate concentration of 1 mol / L.

[0112] S6, High specific energy lithium battery Al-NCM811|Li-(HfNbTiVZr)N-Cu battery cell assembly

[0113] Ten pieces of ultra-thin metal lithium negative electrode high entropy current collector integrated structure Li-(HfNbTiVZr)N-Cu prepared by S3, 11 pieces of positive electrode NCM811-Al prepared by S4 and polyethylene separator were stacked to prepare high specific energy lithium battery cells, and then the cells were placed in pre-punched aluminum-plastic bags. After drying at 100°C for 20 hours, the electrolyte prepared by S5 was injected, and the amount of electrolyte added was 3g / Ah. The prepared Al-NCM811|Li-(HfNbTiVZr)N-Cu battery cells were then subjected to chemical treatment, and the chemical process was as follows: charging at a constant current and constant voltage rate of 0.1C to 4.3V, and discharging at a constant current rate of 0.1C to 3.0V. After the chemical treatment, the exhaust was finally sealed and the label was attached for storage.

[0114] The charge and discharge comparison test of the original copper foil and the ultra-thin metal lithium negative electrode high entropy current collector integrated structure prepared in Example 4 found that when the (HfNbTiVZr)N high entropy nitride coating of the present invention is sputtered on the current collector, the nucleation barrier of lithium is reduced, and the deposition of lithium can be controlled spatially, so that lithium is uniformly deposited on the current collector with the (HfNbTiVZr)N high entropy nitride coating attached. This prevents the free growth of lithium dendrites, thereby avoiding the safety hazards such as internal short circuit of the battery caused by contact between dendrites and the positive electrode. The charge and discharge cycle performance of the metal lithium negative electrode is significantly improved, which is specifically manifested in that the capacity of the battery remains stable as the number of cycles increases, and after 200 cycles, the coulomb efficiency remains at a high level.

[0115] The coulombic efficiency test was performed on the NCM811 full battery of Examples 1-4 of the present invention. The battery was charged to 4.3V at a rate of 0.1C constant current and constant voltage, discharged to 3.0V at a rate of 0.1C constant current, and cycled for 500 weeks at 0.1C (20mA / g). The results are shown in Table 1.

[0116] Table 1 Coulombic efficiency of the deposition of metallic lithium anode on the surface of high entropy current collector and the capacity retention rate of the whole battery

[0117] project Coulomb efficiency Capacity retention after 500 cycles Example 1 97.6% 87.7% Example 2 97.2% 89.4% Example 3 98.5% 85.5% Example 4 99.1% 89.6%

[0118] It can be seen from Table 1 that the coulombic efficiency of metal lithium deposition on the surface of the high entropy current collector in Examples 1-4 of the present invention is higher than 97%. The NCM811 lithium batteries using the ultra-thin metal lithium high entropy current collector integrated structure of the present invention all show excellent cycle stability, and can still show a capacity retention rate of more than 85% after 500 cycles.

[0119] Figure 1 The coulombic efficiency of metal lithium deposition on the surface of the high entropy current collector in Example 1 of the present invention. Figure 1 As shown, the deposition and release coulombic efficiency of metal lithium on the surface of NbMoTaHf-Cu high entropy current collector is 97.61%, and it remains stable for 200 cycles. Compared with its lower coulombic efficiency and unstable cycle on the original copper foil surface, it shows that the high entropy surface designed by the present invention does have a significant improvement in the cycle stability of metal lithium.

[0120] It should be noted that when the present invention involves a numerical range, it should be understood that the two endpoints of each numerical range and any value between the two endpoints can be selected. Since the steps and methods used are the same as those in the embodiments, in order to avoid redundancy, the present invention describes a preferred embodiment. Although the preferred embodiments of the present invention have been described, those skilled in the art may make additional changes and modifications to these embodiments once they know the basic creative concept. Therefore, the attached claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.

[0121] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.

Claims

1. A method for preparing a high entropy current collector for a metal lithium negative electrode, characterized in that: The following steps are involved: Taking the current collector as the substrate, a high entropy alloy target is sputtered on the current collector substrate by a first magnetron sputtering method to construct a high entropy coating; The metal lithium target is sputtered onto the surface of the high entropy current collector by a second magnetron sputtering method to deposit a metal lithium film layer, that is, a metal lithium negative electrode high entropy current collector is obtained.

2. The method for preparing a metallic lithium negative electrode high entropy current collector according to claim 1, characterized in that: The high entropy elements in the high entropy coating are three or more of scandium, titanium, vanadium, chromium, manganese, iron, cobalt, nickel, copper, zinc, yttrium, zirconium, niobium, molybdenum, technetium, ruthenium, rhodium, hafnium, tantalum, tungsten, rhenium, lanthanum, cerium, praseodymium, neodymium, promethium, and samarium. In the high entropy coating, the atomic percentage of each high entropy element is equal, and the sum of the atomic percentage of each high entropy element is 100%.

3. The method for preparing a metallic lithium negative electrode high entropy current collector according to claim 1, characterized in that: The high entropy coating is a high entropy alloy coating, a high entropy alloy oxide coating or a high entropy alloy nitride coating.

4. The method for preparing a metallic lithium negative electrode high entropy current collector according to claim 1, characterized in that: In the process of sputtering the high entropy alloy target on the current collector substrate, the gas for magnetron sputtering is argon, oxygen or nitrogen, and the gas pressure is 0.25Pa-0.35Pa. When the gas for magnetron sputtering is argon, the high entropy coating is a high entropy alloy coating. When the gas for magnetron sputtering is oxygen, the high entropy coating is a high entropy alloy oxide coating. When the gas for magnetron sputtering is nitrogen, the high entropy coating is a high entropy alloy nitride coating. In the process of sputtering the metal lithium target onto the surface of the high entropy current collector, the gas used for magnetron sputtering is argon gas with a gas pressure of 0.25Pa to 0.35Pa.

5. The metal lithium negative electrode high entropy current collector according to claim 1, characterized in that: The current collector substrate is copper foil, polymer-based composite copper foil or aluminum-copper composite substrate.

6. The method for preparing a metallic lithium negative electrode high entropy current collector according to claim 1, characterized in that: The specific steps include: The raw materials of high entropy elements are mixed according to atomic ratios and then ball-milled, and then flash-fired to form high entropy alloy targets, the purity of which is ≥99.99%; A high entropy alloy target is sputtered on a current collector substrate by a winding DC magnetron reactive sputtering method to obtain a high entropy coating, and then a metal lithium target is sputtered on the surface of the high entropy current collector by a winding DC magnetron reactive sputtering method to deposit a metal lithium film layer, that is, a metal lithium negative electrode high entropy current collector is obtained; During the DC magnetron reactive sputtering process, the vacuum degree of magnetron sputtering was 9.9×10 -5 Pa~50×10 -5 Pa, target distance is 20cm~50cm, sputtering temperature is 20℃~30℃, and winding / unwinding speed of the winding roller is 5rpm~10rpm.

7. A preparation method according to any one of claims 1 to 6 for preparing a metallic lithium negative electrode high entropy current collector, characterized in that: In the high entropy current collector, the thickness of the high entropy coating layer is 20nm to 200nm, and the thickness of the metal lithium film layer is 5μm to 30μm.

8. An application of the metal lithium negative electrode high entropy current collector according to claim 7 in a lithium battery, characterized in that: The lithium battery comprises a positive electrode, a diaphragm, a metal lithium negative electrode high entropy current collector and an electrolyte. The positive electrode is one of lithium cobalt oxide, lithium nickel manganese cobalt oxide, lithium nickel aluminum cobalt oxide, and a lithium-rich manganese-based material. The diaphragm is a polyethylene diaphragm or a polypropylene diaphragm. The electrolyte is a mixture of lithium hexafluorophosphate, dimethyl carbonate and diethyl carbonate.

9. The use according to claim 8, characterized in that: The preparation process of the positive electrode includes the following steps: the positive electrode material, Super-P conductive agent and polyvinylidene fluoride are stirred and dispersed in a solvent at a mass ratio of 90:5:5 to form a positive electrode slurry with a viscosity of 1Pa·s to 10Pa·s, the positive electrode slurry is scraped onto the surface of the aluminum foil substrate, and after drying, the positive electrode sheet is prepared by rolling. The prepared positive electrode surface loading is 1mAh / cm 2 ~5mAh / cm 2 .

10. The use according to claim 8, characterized in that: The concentration of lithium hexafluorophosphate in the electrolyte is 1 mol / L to 5 mol / L, and the volume ratio of dimethyl carbonate to diethyl carbonate is 1:1.

Citation Information

Patent Citations

  • Method for preparing thin-layer lithium metal anode for all-solid-state lithium-ion battery based on PVD

    CN105489845A

  • Lithium metal composite electrode with controllable nucleation and growth of lithium metal and preparation method thereof

    CN112117437A

  • Flexible lithium metal battery negative electrode, preparation method thereof and lithium metal battery

    CN112713260A

  • Negative electrode current collector complex, preparation method thereof and lithium metal battery

    CN113488659A

  • Carbon-based loaded high-entropy alloy composite material as well as preparation method and application thereof

    CN115832270A

Cited By

  • Preparation method and application of functional current collector with low thermal shrinkage and high tensile strength

    CN119864424A

  • Method and system for preparing negative current collector under extreme conditions, negative current collector and lithium battery

    CN122338082A